أثر تطبيق اتفاقية (STCW78) وتعديلاتها على التدريب البحري والشهادات البحرية في سورية - ديوب محمد; عثمان سقراط (Latakia University Journal - Economic and Legal Sciences Series, 2018)
تناول البحث الحالي دراسة أثر اتفاقية (STCW78) وتعديلاتها على كل من التدريب والشهادات البحرية من خلال تفريغ وتحليل استبيان، تم توزيعه على المدراء والعاملين في المؤسسة العامة للتدريب التأهيل البحري ومديرية الموانئ العامة، وقد تم هذا التحليل وفق برنامج (SPSS). وبينت النتائج التحليلية في هذه الدراسة وجود أثر ذو دلالة إحصائية لتطبيق الاتفاقية وتعديلاتها على كل من التدريب البحري والشهادات البحرية في سورية، وفق علاقة متينة جداً. وقد أفضى ذلك إلى إسهام تطبيق الاتفاقية في رفع وتحسين كل منهما. The current study examined the impact of the STCW78 agreement and its amendments on both training and marine certificates through the discharge and analysis of the questionnaire, distributed to managers and employees In the General Training Corporation for Marine Rehabilitation and the Directorate of Public Ports. This analysis was carried out according to the SPSS program. The analytical results in this study showed a statistically significant impact of the application of the Convention and its amendments on both maritime training and maritime certificates in Syria, according to a very strong relationship. This has contributed to the implementation of the Convention in improving and promotion each.